Investigating The Theme Of The Short Story Entitled “A Good Man Is Hard To Find” By Flannery O’Connor - Agnes Br; Rajeg, I Made; Maharani, Sang Ayu Isnu (International Journal of Linguistics and Discourse Analytics, 2024)
This article investigates the complex themes in Flannery O'Connor's "A Good Man is Hard to Find" aiming to reveal the narrative's inherent complexity. The main focus is on the central themes of morality and the elusive nature of goodness. O'Connor's extraordinary literary skills, characterized by a distinctive narrative style and technique, are carefully examined to reveal a wide range of characters. Each of these characters grapples with the balance between virtue and moral compromise during what initially seems like an ordinary family trip. At the forefront of this exploration is the grandmother, who is elevated to protagonist status. His flawed moral beliefs and unwavering sense of righteousness become important forces that shape the events that occur. Using a multidimensional analytical approach, this research integrates elements of Southern Gothic literature and religious symbolism to enrich our understanding of O'Connor's storytelling. The findings and discussions section hones in on key themes, including Violence and Grace, Goodness, Punishment and Forgiveness, Familial Conflict and Familial Love, and Moral Decay. The analysis illuminates how the narrative utilizes violence for transformative effects, navigates the ambiguity of goodness, portrays the power of forgiveness amid harsh realities, depicts familial love emerging amidst conflict, and examines perceptions of moral decline. Through such a comprehensive exploration, this study not only deepens our appreciation of O'Connor's thematic choices but also provides insight into the complexity of human nature. This emphasizes the challenges inherent in the pursuit of goodness and moral integrity. The article concludes by highlighting the enduring relevance of “A Good Man is Hard to Find,” encouraging readers to reflect on the timeless themes of morality and the complexity of the human condition